Sufisme Syekh Nawawi dalam Tafsir Marâh Labîd - Kholilurrohman, Kholilurrohman (STAI Al-Aqidah Al-Hasyimiyyah, 2019)
This paper examines whether there are possibilities of the teachings of Sufism as outlined in the tafsir book Mar?h Lab?d, Is there a correlation of Sheikh Nawawi's notes in Sal?lim al-Fudlal? 'with the interpretation of Mar?h Lab?d? The results of this analysis conclude whether there is a interpretation of Mar?h Lab?d as a book of interpretations patterned as Sufism or not. The Sufi Sheikh Nawawi al-Bantani, a multi-disciplinary cleric as Sayyid ?Ulam?? al-Hij?z and Sufism expert. He is a practitioner and writer. His phenomenal work is Sal?lim al-Fudlal? ? ? Syarh Hidayah Al-Adzkiy? ? 'whose entire writing is written with al-Sarraj in al-Luma' definition of Sufism teachings in the book Sal?lim al-Fudlal? '. Popular works, Nash?-ih al-bIb?d Syarh al-Munabbiht ?Al? al-Isti?d?d li Yawm al-Ma'?d, contain pure Sufism to improve morals to Allah, His Messenger, and others. One of his great works, namely Mar?h Lab?d is known as Tafsir al-Nawawi or al-Munir al-Tafsir Li Ma?alim al-Tanzil.